The Relationship between Islamic Philosophy and Sufism and Kalam Science - Didik Himmawan; Zhaskiyah Nur Sabillah; Diana Novianti (Konsultan Jurnal Ilmiah Indonesia, 2024)
Tasawwuf is the essence of a person's feeling of desiring divine presence, inner purification, and peace of mind. Often, Sufis believe that there is a connection between God and humans. They also talk about what humans should do in order to relate to God as closely as possible, both through purification of the soul and spiritual actions. Furthermore, the science of kalam is a field of Islamic science that focuses a lot on the discussion of matters of faith or belief. Then, philosophy provides questions to humans about the existence (essence) of humans, God, and the process of natural creation as well as the theoretical formulation of revelation. The purpose of this research is to find out the relationship between Islamic Philosophy with Sufism and Kalam Science. In this writing we use a qualitative method using library research, the library research process begins with the identification of the topic to be studied and continues with the search for appropriate and relevant literature. The literature can be in the form of theories, the results of previous research to support or test the hypotheses put forward in the study.